The Impacts Of Autonomous learning on English Vocabulary Learning: Virtual Environtment - M. Farkhi Faishol Hakim (IJET (Indonesian Journal of English Teaching), 2021)
There are many differences in sentence structure between English and Indonesian. In this study, the researchers conducted a comparative analysis of past sentence patterns in English and Indonesian. The purpose of this research is to find out the past sentence patterns of English and Indonesian, and the similarities and differences between them. The methods used to conduct research are qualitative research and descriptive research to compare patterns between English and Indonesian past sentence patterns. A high school textbook named "Interlanguage" is used as English data, which Indonesian students generally use and understand, rather than college students' books, while Indonesian data is a translation of the selected English text for each past sentence pattern. This research shows that there are more differences than similarities between the two languages. There are six differences, Namely: 1) Verb form; 2) Irregular verb be; 3) English generally has four past tenses, but Indonesian does not; 4) progress; 5) perfect progress; 6) English has 7 basics In the past, there are 2 sentence patterns in Indonesian. Researchers found some similarities, namely: 1) perfect aspect; 2) sentence pattern arrangement. Since English and Indonesian have more differences in past tense sentence patterns than similarities, it is expected that Indonesian learners will encounter some difficulties in learning English past. Keywords: comparative analysis, past sentences, sentence patterns, English, Indonesian